THE FINDINGS OF THE AUSTRALIAN FITNESS INDUSTRY RISK MANAGEMENT (AFIRM) PROJECT. Issue 7 (11th March 2014) - Keyzer, P; Finch, C; Norton, K; Dietrich, J; Sekendiz, B
Abstract : Background: The AFIRM Project is designed to consider, firstly, how does Australian regulation currently control risk management in the fitness industry and thereby prevent adverse health outcomes and injury, and the legal liability associated with those risks? Secondly, what sustainable changes could be made to Australian regulation for more effective risk management in the health and fitness industry in order to prevent the risk of adverse health outcomes and injury, and the legal liability associated with those risks?. Objective: Our objective is to develop new best practice benchmarks to improve safety in the fitness industry and reduce the risk of adverse health and injury outcomes. Design: After conducting focus groups in four States of Australia using nominal group technique, we developed a survey that was administered to 1178 people. We also conducted observational audits of fitness facilities. Settings: See "Design". Participants: Of the 1 178 survey respondents, 62% were female, the mean age was 40, 46% were self-employed or sole traders and 32% were part-time employees of a fitness facility. Results: Focus group respondents reported (lack of) education, (lack of) supervision, (poor) technique, (defective) equipment, (unsuitable) environment and overcrowding as principal issues in the focus group sessions, while also raising the issues of scope of practice, defective pre-exercise screening, medical risks associated with de-conditioned clients, poor or inappropriate nutritional advice, inadequacy of qualifications and unrealistic expectations of clients as key risks, from their perspective. The survey was designed around these themes and was conducted online in May and June 2013 and promoted through a communications strategy of social media, direct e-marketing and (minor) traditional media. It used 45×6-point Likert scale items (e.g. "How frequently do you observe customers using weights that are too heavy?") that were then factor analysed. The results will be provided.